2006
DOI: 10.1002/crat.200510690
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural characterisation of zinc oxide thin films prepared by sol-gel process

Abstract: Zinc oxide thin films have been prepared on different substrates by the sol-gel method using 2-methoxyethanol solution of zinc acetate dihydrate stabilized by monoethanolamine. The photoluminescence spectra of the films show the band-edge and sub-band transitions. The intensity of the band edge emission peak increases, while the intensity of the deep level emission peak decreases in the films coated on sapphire substrate. Transmittance spectra show that the films are transparent beyond 400 nm. The structural p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 18 publications
4
35
0
Order By: Relevance
“…Recently, Mn-doped ZnO materials have attracted much attention because of their excellent ferromagnetic properties [18] and unique UV-luminescent properties based on radiative recombination of the electron-hole pairs [19,20]. Doping Mn into ZnO offers an interesting way to alter various properties [21,22], for example the band gap of host material can be tuned from 3.37 eV to 3.70 eV. Also it alters the emission properties by providing an efficient channel for the recombination of electron and hole via the do-pant Mn d levels.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Mn-doped ZnO materials have attracted much attention because of their excellent ferromagnetic properties [18] and unique UV-luminescent properties based on radiative recombination of the electron-hole pairs [19,20]. Doping Mn into ZnO offers an interesting way to alter various properties [21,22], for example the band gap of host material can be tuned from 3.37 eV to 3.70 eV. Also it alters the emission properties by providing an efficient channel for the recombination of electron and hole via the do-pant Mn d levels.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments showed that the FWHM values of the etched ZnO films are higher than those of the as-deposited films. In this case, a high FWHM value means that the crystalline structure was incomplete [8][9][10][11][12]. These results indicate that ion bombardment during etching damaged the crystalline structure of the ZnO thin film surface.…”
Section: Resultsmentioning
confidence: 86%
“…The ZnO thin films can be prepared by a variety of methods such as chemical vapour deposition (CVD), RF magnetron sputtering [11], DC reactive magnetron sputtering [12], metal organic chemical vapour deposition (MOCVD), molecular beam epitaxy (MBE) [13], pulsed laser deposition [14], sol−gel process [15], chemical bath deposition, etc. Of these methods, SILAR technique has several advantages over the others such as low cost, safety and easy handling.…”
Section: Introductionmentioning
confidence: 99%